Influence of solvent accessibility and intermolecular contacts on atomic mobilities in hemerythrins. - Sheriff, S (1985)
Thermal factor parameters (B values) have been compared from the refined crystal structures of the myohemerythrin from Themiste zostericola and of the octameric hemerythrin from Themiste dyscrita. These B values, which are directly related to atomic mobilities, were found to correlate rather closely with the solvent accessible areas within the respective crystals. Although protomeric units of the two molecules have exceptionally similar three-dimensional structures, there are marked differences between the patterns of relative atomic mobilities along the polypeptide chains. The differences correspond to lattice and oligomer contacts. An adjustment of the B values based on the fraction of accessible area occluded by contacts yields values that correlate well between the independent subunits and that should pertain more closely to those for the protomer free in solution.